Mechanical and electrical properties of La3+ modified BNKZT ceramics - Pichitchai Butnoi (2019)
© 2019 Trans Tech Publications, Switzerland. In this work, Bi0.5-xLaxNa0.4K0.1Zr0.02Ti0.98O3 (where x = 0, 0.01, and 0.03 mol%) ceramics were prepared by conventional solid-state sintering method, sintered in air at l125°C for 2 h. The mechanical and electrical properties of the sintered ceramic with different La-doping were investigated. The crystalline structure of all ceramics was assessed by X-ray diffraction (XRD) method. Other physical and mechanical properties, i.e. density, porosity, shrinkage, Vickers (HV) and Knoop hardness (HK), and electrical properties were determined. XRD patterns for all samples exhibited a pure perovskite, where coexistence between tetragonal and rhombohedral phases was observed for some composition. The maximum dielectric constant at room temperature was obtained for x = 0.03 ceramic. In addition, the piezoelectric properties were improved and showed the highest d33, Smax and d∗33 values of 189 pC/N, 0.28% and 560 pm/V, respectively for x = 0.01 composition. Furthermore, the optimum values of hardness were observed at this composition.